Dukungan Keluarga dan Pemberian ASI Eksklusif pada Bayi di Puskesmas Mamajang Makassar - Herlianty Herlianty; Siti Aqma Ibrahim; Evi Sri Dahrianti; Ferawati Taherong (FORIKES, 2023)
Breast milk is the first and best food for babies that is scientific in nature, exclusive breastfeeding for babies is only given for 6 months without additional food and other liquids. Family assistance is very important during breastfeeding for babies aged 0-6 months. The purpose of this study was to find out the relationship between family support and exclusive breastfeeding for babies in the working area of the Mamajang Health Center in Makassar. The type of research used is case control using a retrospective approach. The number of respondents in this study was 25 samples and the sample technique used was statistical techniques. The instrument used was a questionnaire about family support by giving exclusive breastfeeding to infants 0-6 months. The results of the analysis in this study used the chi square test with the value obtained p = 0.278 > a value = 0.05, which means that there is no significant relationship between family support and exclusive breastfeeding for babies aged 0-6 months in the Working Area Majang Health Center. The solution for families is to find out more about breastfeeding information for babies so that families also support it and for health workers to pay more attention to baby families in providing education about exclusive breastfeeding.Keywords: family support; exclusive breastfeeding for babies ABSTRAK ASI merupakan makanan pertama dan terbaik bagi bayi yang bersifat ilmiah, Asi ekslusif pada bayi hanya di beri selama 6 bulan tanpa tambahan makanan dan cairan lain. Dukungan keluarga sangat penting selama pemberian Asi pada bayi usia 0-6 bulan. Tujuan penelitian ini adalah diketahuinya, Hubungan Dukungan Keluarga Dengan Pemberian Asi Eksklusif Pada Bayi di Wilayah Kerja Puskesmas Mamajang Makassar. Jenis penelitian yang digunakan adalah case control menggunakan pendekatan retropeksi. Jumlah responden dalam penelitian ini 25 sampel dan teknik sampel yang digunakan adalah teknik statistic. Instrumen yang digunakan adalah lembar kuesioner tentang dukungan keluarga dengan pemberian Asi ekslusif pada bayi 0-6 bulan. Hasil analisis dalam penelitian ini menggunakan uji chi square dengan nilai yang diperoleh p value = 0,278> nilai a=0,05, yang berarti bahwa tidak ada hubungan yang signifikan antara dukungan keluarga dengan pemberian Asi pada bayi ekslusif usia 0-6 bulan di Wilayah Kerja Puskesmas Mamajang. Solusi untuk keluarga, agar lebih cari tahu tentang informasi pemberian ASI pada bayi agar keluarga juga mendukung dan untuk tenaga kesehatan agar lebih memperhatikan keluarga bayi dalam memberikan edukasi tentang pemberian ASI ekslusif.Kata kunci: dukungan keluarga; pemberian asi ekslusif pada bayi